Breast cancer - Barber, Matthew D. (Visual guide for clinicians., 2012)
Instructive exploration of diagnosis and management of disease to aid practising clinicians and trainee doctors Topic-focused, highly illustrated with succint text - provides collection of original images for clinician's desktop Contemporary account of breast cancer diagnosis and treatment.